Global higher education practices in times of crisis : questions for sustainability and digitalization - Hack-Polay, Dieu,; Lock, Deborah,; Caputo, Andrea,; Lokhande, Madhavi,; Salunkhe, Uday, (Emerald Publishing Limited, 2024)
COVID-19 has challenged the international environ of higher education teaching, leading colleagues and institutions across the globe to think outside the box and develop innovative practices suited for turbulent times. But often, these are confined to the local or regional levels. Taking forward the notion of the scholar without borders, Global Higher Education Practices in Times of Crisis provides a critical review of the teaching practices in international higher education in the post-COVID era. Issues and debates about inclusivity, diversity, and cultural representation in the curriculum and classroom are explored through the eyes of the academics who negotiate complex teaching landscapes either on a temporary or permanent basis. The aspiration for universal nuanced teaching practices which reflect individual and national identities, along with newly emerging global ones that represent virtual academic citizenship that cross geographical and political borders, are presented as a foundation on which to instil borderless higher education.